The Economy of Local Television Media Study at Jawa Pos Television (JTV) Banyuwangi Bureau - Aldino Mufakkir Aslam (Proceedings of International Conference on Da'wa and Communication, 2019)
A local television company that was built with the spirit of regional culture, is very much felt by its presence by providing a lot of color in the media industry, especially in television media. The problem discussed in this study is the economic media where the economic pressures can affect the strategy of JTV Banyuwangi in sustaining presence in the media industry. The research uses qualitative research by using an economics media analysis, which would explain how attempts by the JTV Banyuwangi do to preserve its existence. The result of this study has four strategies, 1) guarding human resources available for increased growth and creative levels, 2) the same load of entertainment and news, 3) active on social media, 4) working with cable television companies. The strategies of the JTV Banyuwangi to get for the markets, which is the audience and advertising, this strategy was certainly successful because JTV Banyuwangi has enhanced the position on positioning the markets holdings in relation to another local television.